"The future depends on what we do in the present" - Development positions of EU countries by levels of sustainable development and living standards. - Aleksandra Łuczak; Klara Cermakova; Sławomir Kalinowski; Eduard Hromada; Oskar Szczygieł (PLoS ONE)
Sustainable development and standard of living of households have recently become central topics in economic analysis, scientific research, and public debate. This study aims to evaluate the positions of European Union (EU) countries and the changes occurring between 2016 and 2023 in terms of sustainable development and living standard. A hybrid multi-criteria decision-making process based on the modified positional technique for order of preference by similarity to the ideal solution (MP-TOPSIS) was employed to assess these dimensions. The research utilized data from the Eurostat database for the specified period. Both the standard of living of EU inhabitants and their countries' levels of sustainable development were assessed. The findings revealed a clear relationship between the households' living standards and the degree of sustainable development in EU countries. Furthermore, the analysis highlighted significant differentiation in these levels across countries, alongside a general upward trend throughout the period analyzed.